2020
DOI: 10.1007/s11420-020-09779-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with COVID-19 at a Specialty Orthopedic Hospital Converted to a Pandemic Overflow Field Hospital

Abstract: Background: COVID-19, the illness caused by the novel coronavirus, SARS-CoV-2, has sickened millions and killed hundreds of thousands as of June 2020. New York City was affected gravely. Our hospital, a specialty orthopedic hospital unaccustomed to large volumes of patients with lifethreatening respiratory infections, underwent rapid adaptation to care for COVID-19 patients in response to emergency surge conditions at neighboring hospitals. Purposes: We sought to determine the attributes, pharmacologic and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(8 reference statements)
1
4
0
Order By: Relevance
“… 23 , 24 Considering that the number of PINs employed is generally adequate to manage the trauma patient volume received, our findings that higher patient volumes are associated with higher delays may be attributable to the temporary conversion of PIN responsibilities to patient care, overwhelming of hospital capacity, and conversion of acute care facilities into overflow COVID-19 units to handle surges of infected patients. 25 , 26 , 27 Furthermore, it is worth noting that high-capacity Trauma Centers are generally located in highly populated areas where COVID-19 has had the highest burden on hospitals and further supports our findings of high-volume centers experiencing greater delays in Trauma Center operations. 28 However, our findings indicate that trauma registry activities and performance & quality improvement operations were not significantly impacted during the COVID-19 pandemic compared to pre-pandemic years.…”
Section: Discussionsupporting
confidence: 78%
“… 23 , 24 Considering that the number of PINs employed is generally adequate to manage the trauma patient volume received, our findings that higher patient volumes are associated with higher delays may be attributable to the temporary conversion of PIN responsibilities to patient care, overwhelming of hospital capacity, and conversion of acute care facilities into overflow COVID-19 units to handle surges of infected patients. 25 , 26 , 27 Furthermore, it is worth noting that high-capacity Trauma Centers are generally located in highly populated areas where COVID-19 has had the highest burden on hospitals and further supports our findings of high-volume centers experiencing greater delays in Trauma Center operations. 28 However, our findings indicate that trauma registry activities and performance & quality improvement operations were not significantly impacted during the COVID-19 pandemic compared to pre-pandemic years.…”
Section: Discussionsupporting
confidence: 78%
“…[Correction added on 9 February 2021, after first online publication: In the preceding sentence, the median: (404 (21–50 [9–76]) was changed to (40 (21–50 [9–76])]. Studies reported on patients from China (n = 10) [24, 27, 29, 32, 34–36, 42, 62, 63]; USA (n = 8) [28, 30, 38, 40, 43, 44, 60, 61]; France (n = 4) [25, 37, 46, 48]; Spain (n = 4) [33, 47, 53, 58]; Switzerland (n = 3) [41, 54, 57]; Canada (n = 2) [45, 66]; Denmark (n = 2) [39, 65]; Australia [71]; Belgium [69]; Europe [20]; Germany [72]; Greece [55]; Hong Kong [31]; Iceland [59]; India [50]; Iran [49]; Israel [56]; Italy [16]; Kuwait [51]; Netherlands [73]; Poland [68]; Scotland [52]; Singapore [26]; Sweden [64]; UK [70]; and Yemen [67] (n = 1 each). Reported ICU mortality rates ranged from 0% to 84.6%, with values at both extremes arising from small case series.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid duplication of cases, two earlier reports from the Netherlands [21, 22] and one from Germany [23] were excluded. A total of 52 reports were included in the analysis [16, 20, 24–73], comprising the 31 new reports and 21 of the 24 reports from our earlier review (removing the previous reports from ICNARC, Grasselli et al. and Klok et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a week, our organization began a physical transformation to accommodate COVID-19 patient overflow from a large nearby teaching facility ( Miller et al, 2020 ). Operating rooms and recovery settings were converted into intensive care units (ICUs) to meet anticipated demand for critical care of patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%